(untitled) (Educational Dimension, 2024)
Project competence is essential to the professional education of engineering students. It synchronously affects all three components of future professional activity, forming the ability to be creative, carry out scientific research and apply modern technological solutions. However, there often is a lack of attention to master projecting in educational programs, especially for junior undergraduate students. The article describes the developed educational technology for organising project-based learning (PjBL) in the actual educational process conditions to mould engineering students’ project competence. It was based on incorporating a short module dedicated to mastering the basic principles of PjBL into the existing curriculum. During the module, students developed, executed and publicly defended their projects. The choice of topic was up to the students, provided the project was dedicated to waste management. The mastery of the seven PjBL essential elements was considered an indicator of the level of project competence formation. Conducting research in the current educational process put forward strict limitations regarding the project execution time, their permanent adjustment through feedback, and timely evaluation. Short daily surveys via Google Forms devoted to each lesson topic let one organise permanent feedback between the teacher and students. The effectiveness of the applied technology was evaluated by two more detailed surveys at the beginning and after the end of the training. The understanding of PjBL elements was noticeably improved. The improvement was statistically significant for four elements, while for the remaining three, it was borderline.